ANALISIS PENGARUH PENGETAHUAN DAN TEKNOLOGI INFORMASI TERHADAP KINERJA KARYAWAN (Kasus: Persepsi Karyawan Sektor Industri Jasa di Bandung) - Suharyanto, Suharyanto; Tugiyono, Jentot; Herlina, R Lisye (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2022)
The information technology products (IT products) usage in around Bandung city grows fast recently. The management and the owner of business collect high earnings from these products. It’s caused by high demands especially from activities which using IT products. One of the reasons of application of IT products is to improve the product quality and shortening processing time. These reasons applied not only in manufacturing processes, but also apllied in services jobs. The capability of IT products like computers, internet, smartphones and many application programmes familiar to employees. This article shows the result of the effect of application knowledge and of IT products to performance of services employee around Bandung city. The 125 random samples data of services employees used in this research. The analysis about the effects of application of IT products, skill and knowledge to performance of services employee using multiple linier regression model. The independent variables are IT products and skill and knowledge, the dependent variable is employee performance. The result shows that variables IT products and skill and knowledge gives effects to employee performance significantly, with regression equation Y=0,351X1+0,313X+0,132. Keywords: employee performance information technology, knowledge